Miss. Code Ann. ch. 29, § 1247 (1892) - (:unkn) unknown (My University, 1892)
Ch. 29, § 1247: If any person shall sell, or offer or expose for sale, any toy pistol, or cartridges or caps, or other contrivance by which such pistols are fired or made to cause an explosion, he shall be guilty of a misdemeanor, and on conviction, shall be punished by fine not less than five dollars nor more than twenty five dollars or imprisonment in the county jail not less than three days nor more than thirty days, or both.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES